The Research of Online Chinese Teaching to Ethnic Chinese Children: 华裔儿童线上汉语教学研究 - Na , Zhao (Mandarinable: Journal of Chinese Studies, 2000)
Internet technology promotes the rapid development of the Internet education industry, and the online Chinese teaching model has therefore become a new model of international Chinese education. This paper takes overseas Chinese children as the research object, aiming at the particularity of Chinese teaching for Chinese children, combined with the author's own teaching practice, analyzes the problems existing in the online Chinese teaching process for Chinese children and puts forward relevant suggestions.